IDENTIFYING STUDENTS’ POSSIBLE SOLUTION STRATEGIES WHILE SOLVING QUESTIONS REGARDING THE CONCEPT OF MEAN - ENİSOGLU, Didem and ISİKSAL-BOSTAN, Mine (The Eurasia Proceedings of Educational and Social Sciences, 2017)
The purpose of this study was to investigate solution strategies used by seventh grade students regarding the concept of mean given in bar graph representations. Participants were 233 seventh grade students from two public middle schools in Gelibolu district of Çanakkale. Data were collected via a questionnaire. Students' possible solution strategies regarding the concept of mean were identified through item based in-depth analysis. The results of the study indicated that students used two different solution strategies to solve questions regarding the concept of mean. More specifically, the study indicated that the balance model and the average formula were identified as two solution strategies to solve the questions regarding the mean concept given in bar graph representations.